Jambatan Kedua Sdn Bhd (JKSB) / Liya Natasha Abdul Rasid - Abdul Rasid, Liya Natasha (Universiti Teknologi MARA, Perlis, 2024)
This executive summary encapsulates the transformative 6-month industrial training completed at Jambatan Kedua Sdn. Bhd. (JKSB) within the Human Resource and Administration Department. Commencing on September 1, 2023, and concluding on February 9, 2024, this internship served as a pivotal requirement for the culmination of my studies in Human Resource Management for this semester.As a novice in the professional realm, each moment of this internship provided immeasurable experiences that words cannot fully capture. The accumulation of these experiences, however, has proven invaluable for my future career trajectory. Eager to apply the theoretical knowledge acquired during my studies, I approached this opportunity with enthusiasm and a thirst for new insights. Jambatan Kedua Sdn. Bhd. operates through two distinct divisions: The Operation Division, led by Hussin bin Mohammad, and the Corporate Management Division, under the guidance of Abd Razak bin Abd Rahman. Throughout my internship, I was placed within the Human Resource and Administration Department, under the watchful eye of the Head of HRA Department, Muhammad Hafiz bin Hamzah, and the supervision of Nur Amalina binti Mat Hassan. Tasked with diverse assignments, projects, and committee roles for organizational events, I also engaged in client assistance at the office. In my concluding month of internship, I was honored to be appointed by Mr. Hafiz Hamzah to join the Building and Landscape Unit (BLU) under the guidance of Dr. Farah Alwani, the Head of the Unit. This experience provided me with the opportunity to acquire new knowledge and skills, complementing my day-to-day responsibilities in the Human Resources Administration (HRA) Department. This dual exposure not only broadened my understanding but also enhanced my ability to multitask effectively. While handling employee welfare matters in HRA, I concurrently engaged in tasks related to contractors within BLU. This report meticulously outlines the benefits accrued during the industrial training, shedding light on the skills and knowledge acquired—ranging from problem-solving to multitasking. A significant portion is dedicated to a comprehensive SWOT analysis of Jambatan Kedua Sdn. Bhd. (JKSB), accompanied by an infographic and in-depth discussions of each element. Furthermore, strategic recommendations are provided to sustain strengths, mitigate weaknesses, seize opportunities, and address potential threats. The internship experience has proven to be profoundly useful and rewarding, offering insights into various perspectives and the dynamics of the real working world. This report stands as a testament to the impactful journey undertaken at Jambatan Kedua Sdn. Bhd. (JKSB), and I look forward to leveraging these experiences in my future endeavours.